2003
DOI: 10.1152/jn.01054.2002
|View full text |Cite
|
Sign up to set email alerts
|

Vagal Input to Lateral Area 3a in Cat Cortex

Abstract: Penfield's sensory homunculus included visceral organs at its lateral extreme, and vagal input was recently identified lateral to the intraoral representation in primary somatosensory cortex (S1) of rats. We tested whether vagal input is similarly located in cats where area 3b (equivalent to S1) is clearly distinguishable from adjacent regions. Field potentials were recorded from the intact dura over the left hemisphere using electrical stimulation of the left or right cervical vagus nerve in seven cats. A sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 74 publications
3
16
0
Order By: Relevance
“…For somatosensory system this question is much better investigated. Vagal and splanchnic cortical projections terminated in somatosensory cortical areas were described in many studies 39–43 . It is also well known since early anatomical studies of 19th century 44 that visceral and somatosensory afferents terminate at the same neurons in spinal cord, and thus visceral information may travel to the cerebral cortex using the fibers of somatosensory columns.…”
Section: Discussionmentioning
confidence: 99%
“…For somatosensory system this question is much better investigated. Vagal and splanchnic cortical projections terminated in somatosensory cortical areas were described in many studies 39–43 . It is also well known since early anatomical studies of 19th century 44 that visceral and somatosensory afferents terminate at the same neurons in spinal cord, and thus visceral information may travel to the cerebral cortex using the fibers of somatosensory columns.…”
Section: Discussionmentioning
confidence: 99%
“…In cats, stimulation of the renal nerve resulted in responses of neurons in the periphery of the ventral posterolateral nucleus and the dorsal and lateral posterior complex of the thalamus indicating that these sites process afferent information from the kidneys [44]. Stimulation of the vagus nerve resulted in activity modulation in the lateral primary somatosensory and insular cortices of rats and in the primary somatosensory cortex of cats [45][46][47][48]. In humans,functional imaging techniques have shown that stimulation of the vagus nerve in epileptic patients influences neural activity in the thalamus, the insular cortex and the postcentral gyrus, among other brain regions [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Sensory input projects from the nucleus of the solitary tract via the parabrachial nucleus and ventromedial thalamus to the insular cortex caudal to the taste area 49 . A recent study suggests that vagal afferents may also project to the primary sensory cortex, lateral to the region activated by stimulation within the oral cavity 50 . Connections with hypothalamus, supraoptic nucleus, anterior cingulated cortex, amygdala and their cortical projections contribute to autonomic and emotional responses to visceral stimulation 51,52 .…”
Section: Vagal Afferents and Perceptionmentioning
confidence: 99%